An empirical research about whistleblowing behavior in accounting context - Erkmen, Turhan; Caliskan, Arzu Oezsoezguen; Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2014)
Purpose - The purpose of this study is to analyze whether whistleblowing is a fact among accounting professionals when there is a serious wrongdoing at the workplace and to investigate the differences between accounting professionals about whistleblowing intention according to demographic variables. This paper reviews whistleblowing behavior in the context of professional accounting in Turkey. This study discusses whistleblowing event and analyzes it by using the scenario technique. Design/methodology/approach - Three whistleblowing scenarios were used and participants were asked to indicate the likelihood that the individual in the scenario would blow the whistle. Participants indicated blowing the whistle action on a seven-point likert-type of scale for the given scenario. Findings - The main hypothesis is the differences between whistleblowing behavior of accounting professionals in relation to such demographic characteristics as working conditions, total tenure, gender, age, membership and number of customers according to the scenario. The findings support that accounting professionals' demographic factors are important to understand the whistleblowing behavior from their perspectives. Whistleblowing is experienced among accounting professionals above the average level for each scenario. There are no differences about accounting professionals' whistleblowing behavior in terms of their demographic characteristics (working circumstances, total tenure, age, membership and number of customers) with the exception of gender and age variables. Research limitations/implications - This study's results come with some limitations. One limitation is the low response rate achieved in the data collection process. Another limitation is that this study is conducted among accounting professionals, so these finding results cannot be generalized to other different professionals in Turkey. Practical implications - The findings of the study may get the board of directors' or managers' attention to the point that they should become aware of the importance of whistleblowing in their organizations to encourage employees to report the wrongdoings internally. Social implications - When employees report these wrongdoings outside the organization, corporate reputation of the company can be damaged. This ethical issue should be solved in the context of the organization. Originality/value - This study aims to make several contributions to the accounting and management literature. First, it extends the recent accounting literature on whistleblowing by examining demographic characteristics. Second, most of the studies use questionnaire to collect the data from the participants, but in this study, the authors used the scenario technique that reflects the whistleblowing behavior tendency in a work environment in order to learn accounting professionals' evaluations of whistleblowing behavior.
Keywords: Whistleblowing; Accounting professionals; INTENTIONS; ATTITUDES; ETHICS; Business & Economics